Nilai-Nilai Islam Dalam Tradisi Tingkeban di Kelurahan Ngampel Kota Kediri - Putri, Ayu Septiana; Khayu, Abdul; Aprilia, Try Heni (Institut Agama Islam Ngawi, 2024)
Abstract: Tingkeban is a traditional Javanese ceremony associated with the age of the baby seven months in them womb. The Tingkeban ceremony at seven months of pregnancy is the last ceremony before childbirth, in which prayers are offered for the safety and normal delivery of mother and child.